Genotypic variation in Pneumocystis jirovecii isolates in Britain. Issue 8 (1st August 2005) - Miller, R F; Lindley, A R; Copas, A; Ambrose, H E; Davies, R J O; Wakefield, A E
Abstract : Background: Pneumocystis jirovecii is the cause of Pneumocystis pneumonia (PCP) in immunosuppressed humans. Asymptomatic colonisation with P jirovecii may occur in patients with minor immunosuppression or chronic lung disease. The aim of this study was to describe the molecular epidemiology of P jirovecii in Britain over a period of 12.5 years. Methods: Between January 1989 and July 2001 161 samples of P jirovecii were obtained from patients with PCP (n = 119), patients colonised by P jirovecii (n = 35), and from air spora (n = 6). Genotyping of samples was performed at the mitochondrial large subunit rRNA (mt LSU rRNA). Results: Genotype 1 (38%) was the most frequently identified genotype: genotypes 2 (26.6%), 3 (20.3%), and 4 (5%) were less common. Mixed infection (more than one genotype) was identified in 10% of samples. While genotype 1 was the most frequently detected type in both patients with PCP and those colonised by P jirovecii (38% and 42%, respectively), these groups differed in the relatively lower rate of detection of genotype 4 (2% v 17%) and the higher detection of mixed infection in those with PCP (13% v 3%). Detection of specific genotypes of P jirovecii was associated with the patient's place of residence (p = 0.02). There was no association between specific genotypes and severity of PCP as measured by arterial oxygen tension (p = 0.3). Conclusions: The evidence of clustering of specific genotypes with patient's postcode of residence is consistent with the hypothesis of person to person transmission of P jirovecii via the airborne route. The lack of association between specific mt LSU rRNA genotypes and severity of PCP suggests that this locus is not implicated in the virulence of the organism.